Patient Perspectives on Health Data Privacy and Management: “Where Is My Data and Whose Is It?” - Mart Wetzels; Eva Broers; Peter Peters; Loe Feijs; Jos Widdershoven; Mirela Habibovic (International Journal of Telemedicine and Applications)
New technologies are increasingly evaluated for use within the clinical practice to monitor patients’ medical and lifestyle data. This development could contribute to a more personalized approach to patient care and potentially improve health outcomes. To date, patient perspective on this development has mostly been neglected in the literature. Hence, this study aims to shed more light on the patient perspective on health data privacy and management. Focus groups with cardiac patients were done at the Elizabeth TweeSteden Ziekenhuis (ETZ) in the Netherlands as part of the DoCHANGE project. The focus groups were conducted using a semistructured protocol which was organized around three themes: privacy regulations, data storage, and transparency and privacy management. Five focus groups with a total of 23 patients were conducted. The majority of the patients preferred to have access to their medical data; however, the knowledge on who has access to data was limited. Patients indicated that they do not want to share their medical data with health insurance companies or the pharmaceutical industry. Furthermore, most patients do not see the added value of supplementing their medical dossier with lifestyle data. Current findings showed patients prefer access to and control over own data but that the knowledge concerning data privacy and management is limited. Sharing of non-medical health data (e.g.,, physical activity) was considered unnecessary. Future studies should address patient preferences and develop infrastructure which facilitates medical data access for patients.